Fostering Medical Students’ Leadership and Team Building Skills and Respect toward Other Health Profession through Inter-Professional Education Analysis of Its Possible Application in Indonesian Medical Schools - Lestari, Endang (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2011)
Inter-professional learning is becoming a very hot issue in medical education field in Indonesia nowadays. Many medical faculties carried out discussions about this topic to consider the possibility to apply the method of learning in their own faculties. This writing is a critical review of an article concerning multiprofessional learning in medical field and an analysis of its possible implications to improve the quality f medical education in Indonesia (Sains Medika, 3(1):89-101).